An Approach of Simple Linear Sequential Techniques for Examination Venues Placement in UiTM Pulau Pinang Branch (Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA Perlis, 2019)
Amongst the important module of Examination Management Systems (EMS) is the process of examination venues placement for the courses and students. At Universiti Teknologi MARA(UiTM) Pulau Pinang Branch (Permatang Pauh Campus), this task will be started whenever the timetable of the courses has been announced on the student portal website. The manual method of assigning the venues for each course using Microsoft Excel leads to some major problems such as the unconsciousness of excessive student load in an examination hall and the examination of the same course code was distributed at separate examination halls. Simple Linear Sequential Approach has been introduced to solve the problems and improve the examination management process. The Simple Linear Sequential Approach has been modified by embedding additional variables such as determination of total students by each session of examination and separation of different duration of examination at the same venue of examination. This approach improves and produce better placement of examination venues for the courses and students.